Ion release from calcium and fluoride containing dental varnishes. (4th February 2014) - Cochrane, NJ; Shen, P; Yuan, Y; Reynolds, EC
Abstract Background A range of dental varnishes have been commercialized recently that contain calcium and inorganic phosphate in addition to fluoride. The aim of this study was to analyse the fluoride, calcium and inorganic phosphate ion release from: (1) MI Varnish containing casein phosphopeptide‐amorphous calcium phosphate (CPP‐ACP); (2) Clinpro White containing functionalized tricalcium phosphate (fTCP); (3) Enamel Pro containing amorphous calcium phosphate; (4) Bifluorid 5 containing calcium fluoride; and (5) Duraphat (no added calcium control). Methods The varnishes were applied to a standardized surface area of polyvinyl chloride (n = 7 per group) and immersed in 25 g of distilled deionized water which was changed at 1, 4, 24, 72 and 168 hours. The ion release was determined by ion chromatography and expressed as μmol (cumulative) per gram of varnish. Results All varnishes released measurable fluoride and calcium, however only MI Varnish and Enamel Pro released significant levels of inorganic phosphate. At 24 hours the order of cumulative fluoride release was: 1>3>4>2=5 with 1 significantly higher (p < 0.05) than the rest. At 72 and 168 hours, the cumulative calcium release was: 1>4>3>2=5 with 1 significantly higher (p < 0.05) than the rest. Conclusions MI Varnish containing CPP‐ACP had the highest release of calcium and fluoride ions.